2019
DOI: 10.4038/engineer.v52i1.7340
|View full text |Cite
|
Sign up to set email alerts
|

Application of Recycled PET Fibers for Concrete Floors

Abstract: High consumption of plastics leads to production of large amounts of plastic waste. Plastic is non-biodegradable so its disposal has been a problem. In order to resolve this problem, recycled PET fibers were proposed to be used as reinforcement in concrete. This paper has discussed the effect of adding Polyethylene terephthalate (PET) fiber to the blended cement mixed concrete floor slab panel. This research consists of two main stages. In first stage, different volumes of recycled PET fibers, i.e. 0%, 0.5%, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Nasr et al [ 43 ] reported that 0.25 % of waste plastic fiber improved strength by 16.8 % and 21.5 % at the concrete age of 28 and 56 days. However, the increase in synthetic fiber content in the concrete mixture can reduce linearly the concrete compressive strength [ 76 , 77 ]. Abdulridha et al [ 62 ] investigated the effect of reinforcing the concrete by waste nylon fiber from the rope wire by 0 %, 0.25 %, 0.5 %, and 1 % to the weight of the concrete mixture and found that the replacement of waste rope fiber by 0.5 % improves compressive strength by 22 % compared to the control mixture.…”
Section: Effect Of Wsf On Mechanical Propertiesmentioning
confidence: 99%
“…Nasr et al [ 43 ] reported that 0.25 % of waste plastic fiber improved strength by 16.8 % and 21.5 % at the concrete age of 28 and 56 days. However, the increase in synthetic fiber content in the concrete mixture can reduce linearly the concrete compressive strength [ 76 , 77 ]. Abdulridha et al [ 62 ] investigated the effect of reinforcing the concrete by waste nylon fiber from the rope wire by 0 %, 0.25 %, 0.5 %, and 1 % to the weight of the concrete mixture and found that the replacement of waste rope fiber by 0.5 % improves compressive strength by 22 % compared to the control mixture.…”
Section: Effect Of Wsf On Mechanical Propertiesmentioning
confidence: 99%
“…Among all of the plastic materials, polyethylene terephthalate (PET) is one of the main recycled materials used to perform thermal insulation in buildings [ 56 ]. Many authors have already investigated the suitability of plastic waste in cement and/or concrete [ 57 , 58 ]. It is clear that the use of this type of waste in the construction field may represent an effective solution for reducing the environmental impact of plastics and, thus, to contribute to the development of an increasingly sustainable building industry.…”
Section: Introductionmentioning
confidence: 99%
“…However, what makes PET so important, among the plastics used as reinforcement for concrete, is its recyclability together with the great abundance of postconsumer waste in the form of bottles. e presence of fibres improves the tensile behaviour of concrete thanks to the sewing effect that they have on the cracks [14]. eir action, in fact, is more effective in the postcracking phase, preventing and reducing the propagation of cracks.…”
Section: Introductionmentioning
confidence: 99%